2021
DOI: 10.1111/ijcs.12683
|View full text |Cite
|
Sign up to set email alerts
|

Modeling expenditure differentials of international tourists by targeted utility: A synthesized theoretical and quantile decomposition approach

Abstract: This paper introduces conditional counterfactual quantile decomposition methods to the literature on tourism consumption, where observed expenditure differentials are directly referred to differences in tourists’ targeted utility. Decomposition terms are synthesized with the neoclassical framework of utility‐constrained expenditure minimization, such that their interpretations do not rely on the approximation of tourists’ preferences by typical socioeconomic expenditure determinants. Using survey data from an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Indeed, there were only nine cases which had a negative and statistically significant relationship. The income variable has been found to be significant in most recent research as well (e.g., Correia et al, 2018;Almeida and Garrod, 2021;Alfarhan et al, 2022a).…”
Section: Incomementioning
confidence: 91%
See 3 more Smart Citations
“…Indeed, there were only nine cases which had a negative and statistically significant relationship. The income variable has been found to be significant in most recent research as well (e.g., Correia et al, 2018;Almeida and Garrod, 2021;Alfarhan et al, 2022a).…”
Section: Incomementioning
confidence: 91%
“…The age of respondents is one of the factors most frequently mentioned when trying to explain tourist expenditure albeit without any general agreement among researchers regarding its possible impact. It has had a positive effect on expenditure in a number of studies with older participants being more inclined to spend than younger ones ( Brida and Scuderi, 2013 ; Pellegrini et al, 2021 ; Alfarhan et al, 2022a ). In contrast, however, some other studies have demonstrated the opposite effect ( Bernini and Cracolici, 2015 ; Yang et al, 2021 ).…”
Section: Theoretical Background and Proposed Research Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed information on the quantile regression outputs using this data set are presented inAlfarhan et al (2021aAlfarhan et al ( , 2021b.…”
mentioning
confidence: 99%